The Influence of Cadmium Heavy Metal on Vitamins in Aquatic Vegetables - Widowati, Hening (Makara Journal of Science, 2012)
The absorption of cadmium heavy metal in 3 (three) kinds of aquatic vegetables; water lettuce (Limnocharis flava), water convolvulus (Ipomoea aquatic Forsk.) and watercress (Nasturtium officinale R. Br) was studied to determine the influence of the contents of vitamins A and C. The purpose of this research was to identify the accumulation of cadmium in the organs of the aquatic vegetables, and their influence to the contents of vitamins A and C. This research was conducted by employing the factorial experimental design of randomized block design (RBD) with 3 (three) factors. The data was analyzed by regression to detect the correlation and contribution of cadmium influence on the aquatic vegetables. The accumulation of cadmium in the 3 (three) aquatic vegetables was mainly occured in the stems and leaves. Water lettuce has the highest accumulation of cadmium, followed by water convolvulus and watercress has the least. Cadmium is responsible for the declining levels of vitamins A and C.